Prawo człowieka do integralności - Kędzia, Zdzisław (Wydział Prawa i Administracji UAM, 1989)
The idea of integrity of a human being is the object of interest of the human rights doctrine as well as of psychology and other social sciences. References to it are made i.a. by different currents in personalism or by the social doctrine of the Catholic Church. The American Convention on Human Rights and the African Charter on Human and Peoples' Rights proclaim the protection of integrity of an individual. In documents originating in the United Nations the notion of mental and physical integrity of an individual's personality appeared in connection with considerations on scientific and technological development, which according to the Proclamation of Teheran of 1968, was to be with in the focus of the United Nations' special attention. In the first place, the considerations aim at discovering whether the notion of integrity of a human being gives rise to any separate value to be protected and if so, whether this protection should take the form of a new human rights standard. The first question finds the affirmative answer. The analyses of meanings ascribed to the said notion allow to conclude that the human being's integrity may be described by means of the following words: identity — indyviduality of a human being, his/her psychical and physical autonomy, and psycho-physical equilibrium. As to the second question, the author states that integrity understood in the above way is nowadays protected by many separate, already existing rights, the scope of which may, or rather should, be enriched as the need arises. The protection of the said value can also be seen in a methodological approach, according to which human rights should be expressed in a complex way and their categories should not be arranged in a hierarchical order. Attention should also be paid to establishing a specific protection of human being's integrity by means of the instrument of general principle rather than that of subjective right. The former seems to correspond better with the wide scope and complex contens of the said value, which possesses a character of general category. Besides, in favour of the former instrument speaks also the function such categories play in the human rights protection. Namely, this protection have reached — so to speak — a new twist in the spiral of its development. While at the birth of the human rights idea one dealt just with general categories (life, freedom, property, happiness and equality), they were soon defined in terms of particular rights, very numerous today. The human rights protection became subject to atomization. More and more often an individual who claims his interests is forced to found his/her action not on one human right, nor on several such rights simultaneously, but he/she may even need to reach into the space between the boundaries of separate rights. This is where the present tendency to integrate the human rights protection comes from. In turn, the above general categories, forming the framework of the individual's rights, may perform the function of linking factors in building the said integration. The principles referring to such rights, addressed in the first place to the organs applying the law, may serve as interpretative directives referring to the whole body of human rights and as a basis for interpreting the catalogue of means of the individual's protection when the application of separate rights fails
Right t o integrity of a human being